Dielectric function and thermo-optic coefficients of silicon-doped GaN substrates at elevated temperature from 298 K to 873 K in the UV-Vis-NIR spectrum - Subiao Bian; Xi Chen; Changcai Cui (Scientific Reports)
Abstract Understanding the thermal influence on gallium nitride (GaN) single crystal substrates is critical for the advancement of GaN-based optoelectronic devices. In this study, we comprehensively characterized the thermal effects on the optical properties of silicon-doped GaN substrates using spectroscopic ellipsometry over a broad wavelength range from 250 nm to 1600 nm. The dielectric function of GaN was determined at temperatures ranging from 298 K to 873 K, demonstrating consistent temperature-dependent behavior. The exciton transitions were precisely characterized and modeled using the empirical Varshni expression. Moreover, we report, for the first time, the thermo-optic coefficients across the wide spectrum, parameterized using a Sellmeier model. This work significantly expand the GaN optical properties database beyond thin films and provide essential insights for the design and optimization of next-generation GaN-based optoelectronic devices.